Arsenomics: omics of arsenic metabolism in plants - Tripathi, Rudra Deo; Tripathi, Preeti; Dwivedi, Sanjay; Dubey, Sonali; Chakrabarty, Debasis; Trivedi, Prabodh k. (Frontiers in Physiology, 2012)
Abstract Arsenic (As) contamination of drinking water and groundwater used for irrigation can lead to contamination of the food chain and poses serious health risk to people worldwide. To reduce As intake through the consumption of contaminated food, identification of the mechanisms for As accumulation and detoxification in plant is a prerequisite to develop efficient phytoremediation methods and safer crops with reduced As levels. Transcriptome, proteome and metabolome analysis of any organism reflects the total biological activities at any given time which are responsible for the adaptation of the organism to the surrounding environmental conditions. As these approaches are very important in analyzing plant As transport and accumulation, we termed “Arsenomics” as approach which deals transcriptome, proteome and metabolome alterations during As exposure. Although, various studies have been performed to understand modulation in transcriptome in response to As, many important questions need to be addressed regarding the translated proteins of plants at proteomic and metabolomic level, resulting in various ecophysiological responses. In this review, the comprehensive knowledge generated in this area has been compiled and analyzed. There is a need to strengthen Arsenomics which will lead to develop of tools to develop As-free plants for safe consumption.